Who Are The Microenterprise Owners? : Evidence From Sri Lanka On Tokman V. De Soto - De Mel, Suresh, 1964- 1964- (The World Bank, 2008)
Is the vast army of the self-employed in low income countries a source of employment generation? This paper uses data from surveys in Sri Lanka to compare the characteristics of own account workers (non-employers) with wage workers and with owners of larger firms. The authors use a rich set of measures of background, ability, and attitudes, including lottery experiments measuring risk attitudes. Consistent with the International Labor Organization's views of the self employed (represented by Tokman), the analysis finds that two-thirds to three-quarters of the own account workers have characteristics which are more like wage workers than larger firm owners. This suggests the majority of the own account workers are unlikely to become employers. Using a two and a half year panel of enterprises, the authors show that the minority of own account workers who are more like larger firm owners are more likely to expand by adding paid employees. The results suggest that finance is not the sole constraint to growth of microenterprises, and provides an explanation for the low rates of growth of enterprises supported by microlending